Cognitive Thought Stopping Therapy Towards Depression and Control Negative Thoughts in Post-Stroke Patients - Sutinah, Sutinah (IJNP (Indonesian Journal of Nursing Practices), 2021)
Background: Stroke is the third leading cause of mortality worldwide after coronary heart disease and cancer in developed and developing countries. Psychosocial therapy is important to reduce depression levels and control negative thoughts of post-stroke patients. Objective: This study aims to determine the effect of cognitive thoughts stopping therapy to decrease the levels of depression and increase the ability to control negative thoughts in post-stroke clients. Methods: This study used a quasi-experimental research design. A purposive sampling technique was used with 48 of the total sample. Result: Wilcoxon test results for cognitive thought-stopping therapy (CTST) showed p=0.003; cognitive therapy (CT) showed p=0.003, and thought stopping (TS) showed p=0.002. It indicated that in each treatment group, there were significant differences. Meanwhile, the Kruskal Wallis test showed that the posttest om depression showed p=0.001, Wilcoxon for CTST showed p=0.002, CT showed p=0.003, and thought stopping (TS) showed p=0.002, indicating that in each treatment group, there were significant differences. The Kruskal Wallis test showed that the posttest on the ability to control negative thoughts showed p=0.000. Conclusion: The results showed an effect of therapy on depression levels and the ability to control negative thoughts. Hospitals can implement this study's results to develop mental health services, especially for stroke clients.